2017
DOI: 10.1038/ejcn.2017.55
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplementation with quercetin on plasma C-reactive protein concentrations: a systematic review and meta-analysis of randomized controlled trials

Abstract: Promising experimental studies suggest that quercetin has potential anti-inflammatory effects. However, the results of current clinical trials on quercetin's effects on the C-reactive protein (CRP), a sensitive inflammatory biomarker, are ambiguous. We conducted a meta-analysis of available randomized controlled trials (RCTs) to resolve this inconsistency and quantify the net effect of quercetin on circulating CRP concentrations. A systematic search was performed in several databases including SCOPUS, PubMed-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…A meta-analysis of clinical studies evaluating quercetin actions on cardiovascular protection concludes that quercetin supplementation should be considered as an add-on therapeutic approach [241]. Quercetin doses above 500 mg/day show effects on the C-reactive protein levels [242], and in women with polycystic ovary syndrome, 1g quercetin intake for 12 weeks improved adiponectin-mediated insulin resistance and hormonal profiles [242]. Moreover, in 50 rheumatoid arthritis (RA) patients, 500 mg quercetin supplementation during 8 weeks ameliorates clinical symptoms such as early morning stiffness and pain, disease activity, and TNFα plasma levels [200].…”
Section: Quercetinmentioning
confidence: 99%
“…A meta-analysis of clinical studies evaluating quercetin actions on cardiovascular protection concludes that quercetin supplementation should be considered as an add-on therapeutic approach [241]. Quercetin doses above 500 mg/day show effects on the C-reactive protein levels [242], and in women with polycystic ovary syndrome, 1g quercetin intake for 12 weeks improved adiponectin-mediated insulin resistance and hormonal profiles [242]. Moreover, in 50 rheumatoid arthritis (RA) patients, 500 mg quercetin supplementation during 8 weeks ameliorates clinical symptoms such as early morning stiffness and pain, disease activity, and TNFα plasma levels [200].…”
Section: Quercetinmentioning
confidence: 99%
“…Although the administration of antioxidants to prevent muscle damage is controversial [3][4][5], some recent studies indicate that ingestion of polyphenol-rich extracts for at least three days before exercise and during the following hours/days may improve recovery [6]. Zynamite ® , a mango leaf extract rich in the natural polyphenol mangiferin, and quercetin have antioxidant and anti-inflammatory properties [7][8][9][10], which may prevent EIMD and facilitate recovery [11]. Nevertheless, these two polyphenols have not been studied in combination and the effect of quercetin has been only assessed after chronic administration and with large daily doses (∼1000 mg), which could impair exercise performance or blunt part of the adaptations to training [12].…”
mentioning
confidence: 99%
“…Prior studies in diabetic rats showed quercetin intake decreases hyperinsulinemia, insulin resistance, inflammatory factors, blood pressure, and hyperlipidemia (Mahmoud, Hassan, El Bassossy, & Fahmy, 2013;Rivera, Moron, Sanchez, Zarzuelo, & Galisteo, 2008). In addition, recent meta-analyses have reported the beneficial influences of quercetin administration on inflammation, blood pressure, and serum triglycerides levels in humans (Mohammadi-Sartang, Mazloom, Sherafatmanesh, Ghorbani, & Firoozi, 2017;Sahebkar, 2017;Serban et al, 2016). Some randomized controlled trials (RCTs) have investigated the effects of quercetin on glucose homeostasis in patients with metabolic disorders, whereas the results are conflicted.…”
mentioning
confidence: 99%